2012
DOI: 10.2147/rmhp.s26567
|View full text |Cite
|
Sign up to set email alerts
|

Development of an indoor air quality checklist for risk assessment of indoor air pollutants by semiquantitative score in nonindustrial workplaces

Abstract: BackgroundTo meet the current diversified health needs in workplaces, especially in nonindustrial workplaces in developing countries, an indoor air quality (IAQ) component of a participatory occupational safety and health survey should be included.ObjectivesThe purpose of this study was to evaluate and suggest a multidisciplinary, integrated IAQ checklist for evaluating the health risk of building occupants. This IAQ checklist proposed to support employers, workers, and assessors in understanding a wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…These factors are mainly due to poor response and maintenance by building owners/facilities managers, who are not making the health and safety of their occupants their main priority. This is supported by previous studies that showed poor response of facilities managers to IAQ, only responding once a problem had occurred 3,8,45. Therefore, a proactive and enhancement program is needed for owners/managers to understand the concept of IAQ and the effect of poor building management.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…These factors are mainly due to poor response and maintenance by building owners/facilities managers, who are not making the health and safety of their occupants their main priority. This is supported by previous studies that showed poor response of facilities managers to IAQ, only responding once a problem had occurred 3,8,45. Therefore, a proactive and enhancement program is needed for owners/managers to understand the concept of IAQ and the effect of poor building management.…”
Section: Discussionmentioning
confidence: 55%
“…The spatial element of the data represents the condition of the building and is a major indicator for the IAQ analysis condition, ie, could predetermine IAQ-related symptoms in buildings. To evaluate the cluster, the data was computed to produce an index score as described by Syazwan 3,8…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations